Analysis Of Patient Loyalty At XYZ Hospital, Palembang City - Annisa, Annisa Zahra Kamilah; Yohana, Yohana F. Cahya Palupi Meilani (Dinasti Publisher, 2025)
This study aims to analyze the factors that influence patient loyalty at XYZ Hospital in Palembang City. The factors studied include service quality, patient trust, hospital facilities, patient experience, and medical staff communication. The method used is a quantitative approach with data collection through a survey of hospital patients. A total of 135 patients agreed to provide responses. PLS SEM was used as a method to analyze the data. The results of the analysis indicate that service quality, trust, and patient experience significantly influence patient loyalty, both directly and through mediation of patient satisfaction. This study provides theoretical implications for the development of literature on patient loyalty in the health sector and offers practical guidance for hospital management to improve the overall patient experience.